Analysis Of Determinant Factors Employee Performance Of Directorate General Of Intellectual Property Rights Republic Of Indonesia - Agus Siswanto; Ratih Pratiwi; Dian Rokhmawati; Firdaus Yuni Dharta; Hartanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Examining the effects of leadership style, work motivation, work discipline, and job happiness on employees' performance is the goal of this study. The study's population, which totaled 100 people, was made up of workers. The required sample is gathered using a convenience sampling technique. Facts gathered directly from survey respondents are considered primary data. It is here retrieved directly by responding to a questionnaire. The scale that is widely used in the construction of questionnaires is the Likert scale. The data analysis methods employed in this study are hypothesis testing, conventional assumption testing, and data quality testing (validity and reliability testing). Workplace discipline has a significant impact on how well people perform, according to research findings. Work motivation has a big impact on employee performance. A leader's style does not significantly affect employee performance. Job satisfaction has a substantial impact on employee performance. Work ethics, work motivation, leadership style, and job satisfaction all have a big impact on employee performance. An analysis of the adjusted coefficient of determination (Adjusted R Square) shows that the competence, work discipline, remuneration, organizational culture, and organizational commitment variables may all be utilized to explain the performance variable. Meanwhile, the other difference is influenced by or explained by additional elements outside the purview of this research.